The use of Global Positioning System (GPS) tracking devices to assess movement demands and impacts in Under-19 Rugby Union match - Venter, R. E.; Opperman, E.; Opperman, S. (African Journal for Physical, Health Education, Recreation and Dance, 2011)
This study attempted to use Global Positioning System (GPS) devices to obtain information on elite Under-19 rugby union forward and back players with regard to selected movement patterns, as well as impacts from collisions experienced by players. Seventeen Under-19 male rugby players from a provincial rugby institute in Stellenbosch, South Africa, were studied during five games in a Super League A competition. Data revealed that players covered on average 4469.95 ± 292.25 m during a game. Players spent 72.32 ± 4.77% of the total game time either standing or walking. Props and locks spent more time jogging (26.11 ± 3.77%), compared to outside backs (15.6 ± 2.3%). The outside backs spent more time sprinting (1.11 ± 1.18%) than inside backs (0.72 ± 0.30%) or the front and back row forwards (0.48 ± 0.23% and 48 ± 0.13%) respectively. Back row forwards had the highest total amount of impacts (measured in G-force, g) during the games (683.4 ± 295.04). The inside backs experienced the highest amount of severe impacts (>10g) (12.16 ± 3.18) per match. The intermittent nature of Under-19 rugby union match play, as well as the unique roles and requirements of positional groups, were confirmed. The use of GPS technology also offered valuable insight into the severity of impacts experienced by players in different positions, which was not previously available. An understanding of match-play requirements, as well as the number and intensity of collisions experienced by players, can assist coaches with planning specific training programmes, as well as adequate recovery between training sessions and games